Does manure management regulation work against agglomeration economies? Evidence from French hog production - Carl Gaigné; Julie Le Gallo; Solène Larue; Bertrand Schmitt (European Regional Science Association (ERSA), 2010)
The well-known rise in the geographical concentration of hog production suggests the presence of agglomeration economies related to spatial spillovers and inter-dependencies among industries. In this paper, we examine whether manure management regulation restricting manure application per acre may weaken productivity gains arising from the agglomeration process. We develop a spatial model of production showing that, on the one hand, dispersion is favored when manure is applied to land as a crop nutrient and, on the other hand, agglomeration is strengthened when farmers adopt manure treatment. Estimations of a reduced form of the spatial model with a SHAC procedure applied on 1988 and 2000 French hog production data confirm the role played by the spatial spillovers and the backward and forwards relationships. Results also suggest that manure management regulation does not work against the spatial concentration of hog production, but boosts the role played by spatial spillovers in agglomeration process
Keywords: Q10; Q53; R12; 330; Hog production; Manure management regulation; Agglomeration economies; Spatial Econometrics